Anti‐infective potential of Citrus bergamia Risso et Poiteau (bergamot) derivatives: a systematic review. (24th May 2016) - Cirmi, Santa; Bisignano, Carlo; Mandalari, Giuseppina; Navarra, Michele
Abstract : Infectious diseases remain among the leading causes of morbidity and mortality worldwide, mainly because of the increase of resistance to chemotherapeutic drugs. Nature is the major source of anti‐infective drugs and could represent a font of medicines that may help overcome antibiotic resistance. Recently, the potential antimicrobial effect of certain plant extracts has attracted attention within the scientific community as alternatives to synthetic drugs. Here, we present a systematic review on the anti‐infective properties of bergamot derivatives that highlight the activity of bergamot essential oil against bacteria, mycetes and larvae, as well as the anti‐ Helicobacter pylori effect of bergamot juice and the antimicrobial properties of extracts from bergamot peel. Findings presented herein could be used to develop novel and alternative preventive and therapeutic strategies aimed to overcome antibiotic resistance. Copyright © 2016 John Wiley & Sons, Ltd.